Overcoming Essentialism? Students' Reflections on Learning Intercultural Communication Online - Lotta Kokkonen; Romée Jager; Alexander Frame; Mitra Raappana (MDPI AG, 2022)
The fields of intercultural communication (IC) and intercultural education are in flux and the paradigmatic shift is away from essentialist approaches on culture and interculturality towards seeing IC and interculturality as flexible, fluid, contradictory, political, and ideological constructs. This study presents a virtual exchange project, a joint introductory course on IC between a Finnish university and a French university. One of the objectives of the course was to provide students with a more critical, non-essentialist perspective on interculturality. This study presents an analysis of 32 students' texts (learning logs) that are processed qualitatively using content analysis to find answers to questions of (1) how students make sense of their experience of learning IC through multilingual online interactions, and (2) how different approaches on culture and interculturality are reflected in students' leaning logs. The learning logs are written by participants during their six-week learning experience. The findings indicate that students gained confidence in interacting with people from diverse backgrounds and using multiple languages. How students reacted to and reflected on the more critical perspective on interculturality varied greatly, with many learning logs seeming to juggle between different approaches. The online environment was considered a major source of concern prior and at the beginning of the course, but as the course progressed it did not represent a barrier within the documented experiences. Our analysis aims to help teachers of IC to better address the needs of different learners. We also discuss the challenges and possibilities of a multilingual intercultural virtual exchange with a view to creating safe and motivating spaces for teaching and learning about interculturality.